Biochar‐induced formation of Zn–P‐phases in former sewage field soils studied by P K‐edge XANES spectroscopy. Issue 4 (19th June 2015) - Wagner, Anne; Kaupenjohann, Martin; Hu, Yongfeng; Kruse, Jens; Leinweber, Peter
Abstract Biochar is proposed as a soil amendment for metal immobilization. Studies on former sewage field soils have indicated that biochar addition immobilized Zn, probably by the precipitation of Zn phosphates. Direct evidence of the presence of these mineral phases was still lacking. We investigated the colloidal precipitate obtained after ultracentrifugation of the soil‐water extract a biochar particle and a corresponding bulk soil sample from a sewage field soil that had been amended with 5% (w/w) biochar by P K‐edge XANES spectroscopy. The P K‐edge XANES spectrum of a colloidal precipitate visually resembled spectra of a synthetic Zn phosphate [Zn3(PO4)2] and of hopeite (Zn[6]Zn2[4]PO4·4H2O). Spectra evaluation by principal component analysis (PCA) and linear combination fitting (LCF) confirmed the presence of Zn‐P‐phases in the colloidal precipitate and, to a lesser extent, in the biochar and bulk soil sample. The P speciations varying in differently sampled soil compartments point to a small‐scale heterogeneity of the biochar‐induced P transformation processes.